Effect of Antiretroviral Drugs on the Renal Function of HIV Seropositive Patients attending ISS Clinic of Mulago Hospital, Uganda - Kateregga, John N.; Atuheire, Collins; Nalunga, Justine; James, Ndukui G. (Ann Biotechnol, 2018)
Highly Active Antiretroviral Therapy (HAART) consisting of at least three active drugs against HIV infection has improved HIV/AIDS management since their inception. However, alterations of lipid metabolism due to HAART can result into secondary diabetic and hypertensive renal damage. This study was carried out to assess the effect of antiretroviral drugs on the renal function of HIV seropositive patients by determining the serum levels of Creatinine, Urea and Electrolytes (Na, K, and Cl) of the patients on treatment.
Keywords: HAART; Renal function; Creatinine; Urea; Electrolytes